STUDI KOMPARATIF PERKEMBANGAN USAHA PEDAGANG KAKI LIMA DI KAWASAN SIMPANG LIMA SEBELUM DAN SESUDAH RELOKASI - Purbawati, Reni Shinta Dewi, Dinalestari (JURNAL ILMU SOSIAL, 2014)
In 2010, one of the policies at Semarang Government is to the arrangement of the cadgers with the concept of the food court at Simpang Lima area. A number of shelter used as a culinary center grouped by type of business. This condition is apparently an impact on the development of the business has been run by cadgers. Therefore this study aimed to determine differences in business development both before and after the relocation of cadgers in the area of Simpang Lima Semarang. The study was conducted in the city of Semarang with a sample of 45 traders who occupy the shelter. The research method used was a comparative study. Further variables that all indicators have met the validity will be tested using different test Paired Sample T- Test.The results showed that there are differences in the development of business both before and after the relocation of cadgers in the area of Simpang Lima Semarang better on the indicators of turnover, profit/gain levels, the extent of effort, comfort, venture capital, number of employees and number of consumers. From the factors of business growth can be seen that the factor turnover, profit/gain levels, the extent of the business, venture capital, number of employees, the number of consumers and the number of productivity by traders felt better when compared before relocation than after relocation. Meanwhile as for the comfort factor by merchants considered to be in good condition at the time after relocation.Recommendations can be given the necessity of the payment made at one door/cashier using the concept that each customer can buy in any shop without fear that the buyer does not pay for the food they buy it’s . This concept can be done with the dealer manager agreement with the merchant so good between the consumer and the merchant is not harmed.